A 4+1 ARCHITECTURE FOR IN VIVO ELECTROPHYSIOLOGY VISUAL PROSTHESIS (Journal of Accessibility and Design for All, 2016)
Researchers around the globe are working towards restoring vision to the blind through the development of a visual neuroprosthesis. Overcoming physical, technical and biological limitations represents one of the main challenges for the scientific community and will eventually benefit the wellbeing of the recipients of these devices. Thus, understanding the physiological mechanisms of prosthetic vision plays a key role. In this context, in vivo electrophysiological studies are aiming to shed light on new stimulation paradigms that can potentially lead to improved visual perception. This paper describes a multi-viewpoint architecture of an experimental setup for the investigation of electrically evoked potentials in a retinal neuroprosthesis.